Elite athletes' attitudes towards the use of placebo-induced performance enhancement in sports - Berdi, M.; Köteles, F.; Hevesi, K.; Bardos, G.; Szabo, A. (European Journal of Sport Science, 2015)
While an increasing number of research is devoted to the understanding of placebo effects in sports, athletes' experiences with and attitudes towards the use of placebo for performance enhancement remain poorly understood. In this study, 79 elite athletes from different sports were surveyed on five issues related to placebo use in sports. Results showed that 47% of the athletes have experienced placebo effects in the past. A majority of the athletes (82%) thought that placebos could affect their sports performances. A wider use of placebos in sport settings was endorsed more by those who have experienced placebo effects in the past than those who did not (P = .005). Regardless of past experience with placebo, more than half of the athletes (53%) would accept an unknown but legitimate substance from the coach, and 67% of them would not mind a placebo-linked deception if that was effective. These findings confirm that most elite athletes believe in the power of placebos in enhancing sports performance, and those having a positive past experience exhibit slightly more favourable attitudes in contrast to those without such experiences.